Gender equity and social inclusion in the water-energy-food-ecosystems (WEFE) nexus: Frameworks and tools for moving from resource-centric to people-centric WEFE nexus approaches - Jalonen, Riina; Zaremba, Haley; Petesch, Patti; Elias, Marlène; Estrada-Carmona, Natalia; Tsvuura, Susan; Koirala, Sanju (2022)
This learning module focuses on how to integrate gender equality and social inclusion (GESI) considerations in WEFE approaches to contribute to more effective and equitable WEFE initiatives for current and future generations. Intentionally focusing on GESI in the design, implementation, and monitoring of WEFE initiatives is critical to ensure that these initiatives do not harm – and, rather, benefit – women and vulnerable groups and communities. At the end of this lesson, learners will be able to: (1) Explain the importance of GESI for achieving sustainable development outcomes in the WEFE nexus, (2) Describe common GESI challenges and issues that WEFE projects face, (3) Describe the main steps for better addressing GESI considerations